2019
DOI: 10.18540/jcecvl5iss1pp0026-0032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adsortive Power of Cactus Pear Forage Without Peel for Use in Removal of Common Gasoline in Water Bodies

Abstract: Alternative methods, as adsorption, with use of readily available and low cost materials have been used to remove contaminants in water bodies. Objective of this work was to study adsorptive power of cactus pear forage (Opuntia tuna Mill) biomass without bark as adsorbent for removal of gasoline in water bodies. Material underwent a natural drying process and then comminution to powder form.  In adsorption kinetics study, were evaluated time between 5 and 60 minutes (with a 5-minute interval) and equilibrium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
0
0
Order By: Relevance
“…A similar result was found by Lima et al. (2019) ( Ribeiro Lima et al., 2019 ) for gasoline removal in bodies of water using Opuntia tuna Mill. In this study, the biomass showed a fast kinetics adsorption also in the first minutes and a decrease over time.…”
Section: Resultssupporting
confidence: 89%
“…A similar result was found by Lima et al. (2019) ( Ribeiro Lima et al., 2019 ) for gasoline removal in bodies of water using Opuntia tuna Mill. In this study, the biomass showed a fast kinetics adsorption also in the first minutes and a decrease over time.…”
Section: Resultssupporting
confidence: 89%
“…A caatinga é um bioma exclusivo brasileiro, e possui sua localização principalmente no Nordeste, tendo clima dominante do semiárido, e que ocupa cerca de 10% do território nacional (SOUZA; ARTIGAS; . O semiárido paraibano apresenta uma vegetação que possui como características boa adaptabilidade e resistência a longos períodos de estiagem, devido à pouca distribuição hídrica da região (SILVA, 2019). A algaroba (Prosopis juliflora), é uma espécie originária do Peru, tendo se adaptado ao Nordeste brasileiro, por possuir resistência à estiagem e boa adaptação às condições adversas.…”
Section: Btxunclassified